2006
DOI: 10.4049/jimmunol.176.8.4979
|View full text |Cite
|
Sign up to set email alerts
|

ASC Directs NF-κB Activation by Regulating Receptor Interacting Protein-2 (RIP2) Caspase-1 Interactions

Abstract: Receptor interacting protein-2 (RIP2) is a caspase recruitment domain (CARD)-containing kinase that interacts with caspase-1 and plays an important role in NF-κB activation. Apoptosis-associated speck-like protein containing a CARD (ASC) is a PYRIN and CARD-containing molecule, important in the induction of apoptosis and caspase-1 activation. Although RIP2 has also been linked to caspase-1 activation, RIP2 knockout animals fail to show a defect in caspase-1-mediated processing of proIL-1β to its active form. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
105
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(111 citation statements)
references
References 49 publications
(52 reference statements)
4
105
1
1
Order By: Relevance
“…Our findings may explain the profound phenotype of caspase-1-deficient mice, which, unlike IL-1␤ and IL-18 knockout (KO) mice, and as recently shown in IL-1␤/IL-18 double KO mice (26), are completely resistant to the effects of LPS (27)(28)(29) and are also highly susceptible to infection with pathogens such as Escherichia coli (30,31). Similar to our study, others have shown defects in LPS responses in caspase-1-deficient macrophages such as induction of TNF, IL-6, and IL-1␣ (20,29,31). TNF production in response to LPS was not affected by a neutralizing antibody to IL-18 or in IL-1␤-deficient mice (32,33).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our findings may explain the profound phenotype of caspase-1-deficient mice, which, unlike IL-1␤ and IL-18 knockout (KO) mice, and as recently shown in IL-1␤/IL-18 double KO mice (26), are completely resistant to the effects of LPS (27)(28)(29) and are also highly susceptible to infection with pathogens such as Escherichia coli (30,31). Similar to our study, others have shown defects in LPS responses in caspase-1-deficient macrophages such as induction of TNF, IL-6, and IL-1␣ (20,29,31). TNF production in response to LPS was not affected by a neutralizing antibody to IL-18 or in IL-1␤-deficient mice (32,33).…”
Section: Discussionsupporting
confidence: 77%
“…4C Right, lane 3). THP-1 cells display caspase-1 activation in response to LPS alone and thus do not require costimulation with ATP (19,20). In mouse macrophages, treatment with LPS led to the appearance of an additional form of Mal that was 2.5 kDa smaller in molecular mass than the major form of Mal (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…29 Consistent with a role for ASC as an inhibitor for caspase-1/RIP2-induced NF-kB activation, siRNA-induced knockdown of ASC in THP-1 cells leads to higher NF-kB activation levels, while caspase-1 activation and release of mature IL-1b are diminished. 29 Altogether, these results suggest that caspase-1 may contribute to pro-IL-1b processing through its enzymatic activity, while its interaction with RIP2 induces NF-kB activation. Furthermore, ASC may function as a switch that directs caspase-1 away from RIP2-mediated NF-kB activation towards the maturation of pro-IL-1b in the inflammasome complexes.…”
mentioning
confidence: 64%
“…27 Recently, this caspase-1/RIP2 interaction was shown to be modulated by the adaptor molecule ASC, which also interacts with caspase-1 via its CARD. 29 ASC interferes with the caspase-1/RIP2 interaction and inhibits the subsequent NF-kB activation in a dose-dependent fashion, while stimulating caspase-1-dependent pro-IL-1b maturation. 29 Consistent with a role for ASC as an inhibitor for caspase-1/RIP2-induced NF-kB activation, siRNA-induced knockdown of ASC in THP-1 cells leads to higher NF-kB activation levels, while caspase-1 activation and release of mature IL-1b are diminished.…”
mentioning
confidence: 99%
See 1 more Smart Citation